Transformasi Digital Meningkatkan Kinerja Keuangan Koperasi di Kota Pontianak - Perdhiansyah, Perdhiansyah; Kusmana, Endang (Jurusan Akuntansi Politeknik Negeri Pontianak, 2024)
The digitalization of cooperative services the convenience, speed of service, comfort, and security are the main goals. for members when transacting with the cooperative. Improved financial performance illustrates a good level of financial health. When a process is assessed and monitored over time, the result is its performance. Knowing how the digitalization of services affects the financial performance of cooperatives in Pontianak City is the main objective of this research. This research uses a descriptive research strategy with quantitative methods. This research sample consists of all financial reports produced by institutions that have utilized the digitalization of cooperative services. The research results prove that digitalization of services has an effect on financial performance (ROA, ROE, BOPO). The digitalization of services has a major impact on the financial performance of cooperatives which grows along with advances in technology. This research is limited to the geographical area of Pontianak, so the results may not be generalizable to cooperatives in other locations.